La moneda napolitana de Fernando el Católico, documento propagandístico de la unidad de las coronas. - Francisco Olmos, José María de (Revista General de Información y Documentación, 2001)
A study and assessment of the union of the Crowns of Castille and Ara gon in the persons of the Catholic King and Queen and the use of coinage as poli tical propaganda of this union, with a special analysis in the case of Naples.
Keywords: Money; Coinage; Catholic King and Queen; Naples